PETROGRAPHY, TRACE ELEMENT GEOCHEMISTRY, AND DOLOMITIZATION MODEL - JHIMPIR DOLOMITE, SINDH, PAKISTAN (Biological Sciences - PJSIR, 2004)
Dolomites of Jhimpir area have been examined petrographically and geochemically to observe and characterize the process and extent of dolomitization. These are petrographically classified as calcitic dolomite and dolomitic lime- stones. The texture of dolomite is idiotopic. Most of the dolomite rhombohedrons are fine to medium grained and zoned. The replacement of biomicritic carbonate rocks (Laki Limestone of Early Eocene age) by Mg and Fe-rich solutions is observed in thin section. Major and trace elements have been analyzed in order to assess the compatibility of these elements with dolomite. The average MgO content in the samples close to small fault is between 16 and 17 % and decreases from the fault outwards, down to 5 to 4 %. The Fe, Mn, Na and K contents exhibit a positive correlation with increasing dolomitization, whereas, it correlates inversely with Sr. This paper provides evidence that the dolomites of the Jhimpir area are derived from epigenetic replacement.